Testosterone Recovery Profiles After Cessation of Androgen Deprivation Therapy for Prostate Cancer. Issue 6 (9th May 2019) - Nascimento, Bruno; Miranda, Eduardo P.; Jenkins, Lawrence C.; Benfante, Nicole; Schofield, Elizabeth A.; Mulhall, John P.
ABSTRACT: Introduction: Androgen deprivation therapy (ADT) is frequently used in the treatment of prostate cancer worldwide. Variable testosterone (T) recovery profiles after ADT cessation have been cited. Aim: To evaluate T recovery after cessation of ADT. Methods: We reviewed our institutional prospectively maintained database of patients with prostate cancer who received ADT. Serum early morning total T (TT) levels, collected at baseline and periodically after ADT cessation, were analyzed. Patient age, baseline T level, duration of ADT, and presence of diabetes and sleep apnea were selected as potential predictors of T recovery. 3 metrics of T recovery after 24 months of ADT cessation were analyzed: return to non-castrate level (TT > 50 ng/dL), return to normal (T > 300 ng/dL), and return back to baseline level (BTB). Multivariable time-to-event analysis (Cox proportional hazards), χ 2 test, logistic regression model, and Kaplan-Meier curve were performed to define impact of the above predictors on time and chance of T recovery. Main Outcome Measures: Time and chance of T recovery to non-castrate level (TT > 50 ng/dL), return to normal (T > 300 ng/dL), and return BTB. Results: 307 men with a mean age of 65 ± 8 years were included. Mean duration of ADT was 17 ± 25 months, and median follow-up was 31 ± 35 months. Mean TT values were 379 ng/dL at baseline and 321 ng/dL at >24 months. At 24 months after cessation of ADT, 8% of men remained at castrate level, 76% returned to TT >300 ng/dL, and 51% had returned BTB. Lower baseline T levels (TT < 400 ng/dL) and ADT duration >6 months were associated with a lower likelihood of recovery to normal TT at 24 months. Age >65 years and receiving ADT for >6 months were significantly associated with a slower T recovery. Clinical Implications: T recovery after ADT is not certain and may take longer than expected. Considering the range of side effects of low T, we believe that these findings must be discussed with patients before initiating such therapies. Strengths & Limitations: Our strengths consisted of a relatively large database, long follow-up, and clinically meaningful endpoints. Limitations included the retrospective design of the study. Conclusion: T recovery rates after ADT cessation vary according to patient age, ADT duration, and baseline T levels. Approximately one-quarter of patients failed to normalize their TT level, and one-tenth of men remained at castrate levels 24 months after ADT cessation.